AKTIVITAS ANTIBAKTERI DAN ANTIBIOFILM FRAKSI AIR DAUN KRATOM (MITRAGYNA SPECIOSA) - Lukman Mahdi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Inadequate infection management poses a significant risk of complications, further exacerbated by biofilm-associated infections that lead to therapeutic failure and recurrence. Consequently, the development of novel antibacterial-antibiofilm agents is critical. Natural products offer substantial potential due to their diverse active compounds, notably Kratom leaves (Mitragyna speciosa), which have a long-standing history in traditional medicine. This study aims to evaluate the antibacterial and antibiofilm potential of the aqueous fraction of M. speciosa against Staphylococcus aureus and Escherichia coli. The methodology involved ethanol extraction of the leaf powder, followed by sequential fractionation to isolate the aqueous fraction. Antibacterial activity was assessed using the disk diffusion method, while antibiofilm efficacy was determined via the microbroth dilution method. Results indicated that aqueous fraction of M. speciosa inhibited the growth of S. aureus and E. coli, at concentrations of 5–25%. Antibiofilm assays revealed that the inhibitory effects of aqueous fraction of M. speciosa were dose-dependent. The aqueous fraction of M. speciosa at 1% concentration demonstrated effective inhibition across all three biofilm phases of S. aureus. Conversely, for E. coli, the maximum inhibitory effect was observed exclusively during the eradication phase. These findings confirm that the aqueous fraction of M. speciosa holds strategic potential for development as a natural antibacterial-antibiofilm agent.